Analysis of Charismatic Leadership in the Development of Islamic Culture in Schools: An Analytical Study of SMPIT AL ITQON - Bayan Rahman; Hasyim Asy’ari; Jejen Musfah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the role of charismatic leadership in developing an Islamic school culture at SMPIT Al Itqon. Using a descriptive qualitative approach, data were collected through in-depth interviews with the principal, teachers, students, and staff, as well as supporting document analysis. The findings reveal that the principal plays a pivotal role in fostering an Islamic culture through inspirational leadership, persuasive communication, and exemplary behavior. Key strategies include integrating Islamic values into school activities, such as daily Quran memorization, congregational prayers, and regular Islamic studies. The positive impact of this leadership is reflected in increased discipline, cohesion, and the internalization of Islamic values among all school members. Despite challenges in aligning the vision, the principal effectively addressed these through intensive communication and active involvement. This study provides valuable insights into how charismatic leadership can strengthen Islamic school culture and contribute to shaping a generation with strong character.